Cutting up the climbers: Evidence for extensive polyphyly in Friesodielsia (Annonaceae) necessitates generic realignment across the tribe Uvarieae. Issue 1 (23rd February 2012) - Guo, Xing; Hoekstra, Paul H.; Tang, Chin Cheung; Thomas, Daniel C.; Wieringa, Jan J.; Chatrou, Lars W.; Saunders, Richard M.K.
Abstract: Friesodielsia and the closely related genera Dasymaschalon, Desmos, Exellia, Gilbertiella and Monanthotaxis (Annonaceae subfamily Annonoideae tribe Uvarieae) are taxonomically problematic, with obscure generic delimitations and poorly known phylogenetic relationships. The present study addresses the polyphyletic status of Friesodielsia, using two nuclear and five chloroplast DNA regions to resolve this taxonomic confusion by circumscribing strictly monophyletic genera across the tribe. Bayesian, maximum likelihood and maximum parsimony analyses using a broad taxon sampling (101 taxa) reveal that Friesodielsia species form five robust and morphologically distinct clades. In order to ensure strict monophyly of genera, we restrict the generic name Friesodielsia to an exclusively Asian clade, and the African species that were formerly included in the genus are transferred to Afroguatteria, Monanthotaxis and Sphaerocoryne, necessitating ten new nomenclatural combinations. Schefferomitra, a monospecific genus from New Guinea, is shown to be congeneric with Asian Friesodielsia, and the nomenclatural implications of this are discussed. Two monospecific genera, Exellia and Gilbertiella, are furthermore synonymised with Monanthotaxis, necessitating two additional nomenclatural changes. New generic descriptions are provided for Dasymaschalon (ca. 27 species), Desmos (ca. 22 species), Friesodielsia (ca. 38 species) and Monanthotaxis (ca. 94 species) to reflect these revised circumscriptions.